Du Pont System Analysis In Measuring Financial Performance Of Pharmaceutical Companies Listed On The Indonesia Stock Exchange (Idx) - Tania S, Dessy; Rumiasih, N. A.; Riani, Desmy; Prasetia, Angga (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
This study aims to determine the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The analysis in this study uses the Du Pont system, namely Net Profit Margin, Total Assets Turn Over and Return On Investment. The data used in this study is sourced from the Balance Sheet and Income Statement. Based on the results, it can be said that PT Darya-Varia Laboratoria Tbk, PT Kalbe Farma Tbk, PT Tempo Scan Pacific Tbk and PT Industri Jamu and Pharmacy Sido Muncul Tbk still lack efficiency in managing their assets so that they get a low score on Return On Investment, but PT Industri Jamu and Pharmacy Sido Muncul managed to get an Net Profit Margin value above the average.